2014
DOI: 10.1039/c4ra05936k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reactive species using various gas plasmas

Abstract: In this study, atmospheric nonequilibrium plasmas were generated with six gas species using a multi-gas plasma jet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 37 publications
7
145
0
Order By: Relevance
“…Accordingly, in the present, each reactive species generated by cold atmospheric plasma irradiation was detected using ESR spectrometry, which revealed that the yield of radicals was increased in an irradiation-time-dependent manner [25]. Nevertheless, because of the existence of medium and very short life time of radicals, it is unlikely that these radicals affected the cells directly.…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, in the present, each reactive species generated by cold atmospheric plasma irradiation was detected using ESR spectrometry, which revealed that the yield of radicals was increased in an irradiation-time-dependent manner [25]. Nevertheless, because of the existence of medium and very short life time of radicals, it is unlikely that these radicals affected the cells directly.…”
Section: Discussionmentioning
confidence: 87%
“…and Takamatsu et al. described the detection of radical species in plasma‐treated liquids by using various spin traps . The concentrations of the ⋅OH and ⋅OOH radical adducts of 5‐ tert ‐butoxycarbonyl‐5‐methyl‐1‐pyrroline N ‐oxide (BMPO) and 5,5‐dimethyl‐1‐pyrroline N ‐oxide (DMPO) spin traps were measured in liquid samples by Reuter and co‐workers .…”
Section: Introductionmentioning
confidence: 99%
“…28 The agent was dissolved in a phosphate-buffered saline (-) (PBS(-)) solution, which had a pH of 7.5, and a fixed DMPO concentration of 200 mM. 29 Plasma treatments of 200 ”L solutions were conducted at a 6 mm distance between the plasma source outlet and liquid surfaces with a flow rate of 0.3 L/min for 10 s. The amount of reactive species was calibrated with spin adducts of 2,2,6,6-tetramethylpiperidine 1-oxyl, which identified the amount of OH radical. Results showed that helium plasma generated the largest amounts of OH radical at 110 ”M, as shown in Fig.…”
Section: -11mentioning
confidence: 99%